Pengembangan Autentic Assessment Berbasis Proyek Dengan Pendekatan Saintifik Pada Praktikum Biologi - Lilis Lismaya; Ilah Nurlaelah; Handayani; Rahma Widiantie; Ina Setiawati (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2025)
This study aims to develop an authentic assessment and analyze the implementation of a project-based authentic assessment with a scientific approach in biology practicum. The research method employed was Research and Development (R&D) using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) design model. The results showed that, based on expert validation, the content expert evaluation yielded a score of 85.27% and the media expert evaluation yielded 80.35%, indicating that the developed authentic assessment is valid and suitable for use. The practicality test revealed that the use of project-based authentic assessment obtained a percentage score of 83.34%, categorized as practical. The practicality indicators measured included ease of use, clarity of instructions, adequacy of allocated time, and the suitability of the assessment format to user needs. The effectiveness test indicated that the use of project-based authentic assessment obtained a percentage score of 83.35%, categorized as highly effective. The effectiveness indicators measured included the assessment’s ability to optimally measure learning outcomes, the alignment of project tasks with learning objectives, the improvement of students’ skills, and the achievement of learning outcomes as targeted. The findings of this study recommend the use of project-based authentic assessment for learning activities in all practicum courses within the Biology Education study program.